Frame synchronization techniques and jitter generation : analysis, modelling and enhancement - Walker, Jacqueline (Curtin University, 1997)
Synchronization means the aligning of the significant instants of one signal to the significant instants of another. In digital systems, where timing transfer between systems is required, synchronization is an important function. In this thesis new results on the performance and design of synchronization processes are presented. An inescapable consequence of the synchronization of external autonomous inputs in digital systems is the possibility of failure of digital devices used to capture the external signal. The anomalous behaviour of these devices is referred to as metastability. The most commonly used approach to controlling the problem of metastability is the use of synchronizers. A synchronizer can be designed to reduce the probability of metastable: failure but cannot eliminate it altogether. New high performance synchronizer designs are presented and analysed in this thesis. Another consequence of synchronization is the resulting disturbance of the significant epochs of timing signals. This disturbance is referred to as jitter. The characterization of jitter produced in synchronization processes is important in the design of digital systems. In this thesis, jitter characteristics are derived for two important applications that arise in digital communications systems. The characterization provides new insight into the dependence of the jitter on system parameters.